2021
DOI: 10.1287/isre.2020.0960
|View full text |Cite
|
Sign up to set email alerts
|

The Return on Information Technology: Who Benefits Most?

Abstract: Information and communication technology (ICT) has continuously reshaped the way in which businesses operate. Yet opinions among economists about the returns to ICT, especially at the aggregate level, are divided. We exploit business-to-business transaction panel data from ICT producers to construct ICT capital stocks for a large sample of Belgian firms. This allows us to estimate the returns to ICT at the firm level and to investigate how firm-level ICT investments affected aggregate gross domestic product an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 81 publications
(93 reference statements)
0
5
0
Order By: Relevance
“…In the literature, the impact of technology on enterprise performance presents different results: (1) IT payoff: technologies have positive effects on performance (Devaraj and Kohli, 2003;El-Tamimi et al, 2012;Brynjolfsson and McElheran, 2016;Ilmudeen et al, 2019;Zhang et al, 2019;Dhyne et al, 2020;Terence et al, 2020;Wei and Sun, 2021;Xuan and Zhang, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature, the impact of technology on enterprise performance presents different results: (1) IT payoff: technologies have positive effects on performance (Devaraj and Kohli, 2003;El-Tamimi et al, 2012;Brynjolfsson and McElheran, 2016;Ilmudeen et al, 2019;Zhang et al, 2019;Dhyne et al, 2020;Terence et al, 2020;Wei and Sun, 2021;Xuan and Zhang, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…, 2012; Brynjolfsson and McElheran, 2016; Ilmudeen et al ., 2019; Zhang et al. , 2019; Dhyne et al ., 2020; Terence et al ., 2020; Wei and Sun, 2021; Xuan and Zhang, 2021). (2) IT paradox: the application of technology may not really improve performance (Sun et al.…”
Section: Introductionmentioning
confidence: 99%
“…Positive effects of digitalization are found already in the early 1990s, e.g. by Brynjolfsson and Hitt (1995) and are confirmed in studies by Cette et al (2022), Dhyne et al (2021), and Schivardi and Schmitz (2020). Some papers Moreover, the use of digital technologies such as the Internet or e-commerce applications might reduce information and coordination costs, thus reducing trade costs.…”
Section: Related Literaturementioning
confidence: 83%
“…Firms need skilled personnel to install and operate their ICT investments. Using Belgian data, Dhyne et al (2020) found such investments generate substantial productivity returns, but many firms still seem to be underinvested in ICT. Gal et al (2019) found that digital technologies might well have contributed to the growing dispersion in productivity performance across firms, and that laggard firms need more access to (digital) skills.…”
mentioning
confidence: 99%
“…Nevertheless, we can still conclude that, particularly for the manufacturing sector, the elasticities are higher for large firms compared to all firms combined. This means that not only do large firms benefit more from ICT fixed investment (Dhyne et al 2020), but large firms also benefit more from human capital investment.…”
mentioning
confidence: 99%